The effect of endosulfan bioaccumulation on the growth of carp, Cyprinus carpio LINN. - Taufik, Imam; Supriyono, E.; Nirmala, K. (Indonesian Society of Scientific Aquaculture (ISSA), 2009)
This research was done in order to determine the effect of endosulfan biaccumulation on the growth of carp (Cyprinus carpio). This research was conducted in 40 l of glass aquaria, the initial weight of carp was 0.81±0.098 g/fish, and the pesticide endosulfan with active ingredient of 350 g/l was used as test solution. Preliminary research was conducted with bioassay test to assess LC50-96h of endosulfan for carp, and then the fish were exposed to some series of exposure concentration, those are 10; 30; and 50% of LC50-96h value or 0.24; 0.72; and 1.2 mg/l for 12 weeks. Endosulfan residue analysis in the water and the body of the fish was conducted after: 0, 4, 12, 24, 48, 96, 144, 192, 264 of exposure hours by using liquid gas chromatography (LGC). Body weight of fish was measured weekly. This study resulted that endosulfan was very toxic to the carp with LC50-96h value was 2.42 (2.206-2.652) mg/l. Endosulfan bioaccumulation of exposure concentration of 0.24; 0.72; and 1.20 mg/l were 67.93; 119.21; and 141.19 mg/kg respectively. Bioaccumulation of 119,21mg/kg significantly inhibit the growth of carp. Keywords: endosulfan, bioaccumulation, growth, carp ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh biakumulasi insektisida endosulfan terhadap pertumbuhan ikan mas. Wadah penelitian berupa akuarium kaca, hewan uji adalah ikan mas berukuran 0,81±0,098 g/ekor, bahan uji berupa formulasi insektisida dengan bahan aktif endosulfan 350 g/l. penelitian diawali dengan uji hayati untuk menentukan nilai LC50-96 jam endosulfan terhadap ikan mas, selanjutnya dilakukan pemaparan ikan mas selama 12 minggu dalam air dengan konsentrasi endosulfan yang berbeda, yaitu: 10, 30, dan 50% dari nilai LC50-96 jam atau sebesar 0,24; 0,72; dan 1,20 mg/l. Analisis residu endosulfan dalam sample air dan ikan dilakukan setelah waktu pemaparan 0, 4, 12, 24, 48, 96, 144, 192, dan 264 jam dengan menggunakan kromatografi gas cair (GC), pengukuran bobot ikan dilakukan setiap minggu dengan menimbang berat total. Hasil penelitian menunjukkan bahwa insektisida endosulfan sangat toksik terhadap ikan mas dengan nilai LC50-96 jam sebesar 2,42 (2,206-2,652) mg/l, bioakumulasi endosulfan pada konsentrasi perlakuan 0,24; 0,72; dan 1,20 mg/l secara berturut-turut adalah 67.93; 119,21; and 141,19 mg/kg. Bioakumulasi sebesar 119,21mg/kg secara nyata menghambat pertumbuhan ikan mas. Kata kunci: endosulfan, bioakumulasi, pertumbuhan, ikan mas